2019
DOI: 10.3390/ijerph17010138
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces Acute Liver Injury by Inhibiting Nrf2 and the Role of NF-κB, NLRP3, and MAPKs Signaling Pathway

Abstract: Acute Cadmium (Cd) exposure usually induces hepatotoxicity. It is well known that oxidative stress and inflammation causes Cd-induced liver injury. However, the effect of nuclear factor erythroid 2-related factor 2 (Nrf2) in Cd-induced liver injury is not completely understood. In this study, we observed Cd-induced liver damage and the potential contribution of Nrf2, nuclear factor-κB (NF-κB), Nod-like receptor 3 (NLRP3), and mitogen-activated protein kinases (MAPKs) signaling pathways. Changes in serum transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Previous studies have reported that the redox-responsive transcription factor Nuclear factor-E2-related factor 2 (Nrf-2) and the anti-oxidant enzyme Heme Oxygenase-1(HO-1) play a crucial role in the regulation of oxidative stress during the pathogenesis of liver injury ( Ge et al, 2017 ; Saeedi et al, 2020 ). When activated by the oxidative stress, Nrf-2 can transfer from the cytoplasm into the nucleus, and then binding with the antioxidant responsive elements (AREs), leading to the transcription of HO-1 and some other anti-oxidative genes ( Loboda et al, 2016 ; Liu et al, 2019 ). In addition to HO-1, the superoxide dismutase (SOD) and glutathione peroxidase (GSH-px) also play an important role in the protection of cells against oxidative damage as anti-oxidative enzymes ( Olsvik et al, 2005 ; Damiano et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the redox-responsive transcription factor Nuclear factor-E2-related factor 2 (Nrf-2) and the anti-oxidant enzyme Heme Oxygenase-1(HO-1) play a crucial role in the regulation of oxidative stress during the pathogenesis of liver injury ( Ge et al, 2017 ; Saeedi et al, 2020 ). When activated by the oxidative stress, Nrf-2 can transfer from the cytoplasm into the nucleus, and then binding with the antioxidant responsive elements (AREs), leading to the transcription of HO-1 and some other anti-oxidative genes ( Loboda et al, 2016 ; Liu et al, 2019 ). In addition to HO-1, the superoxide dismutase (SOD) and glutathione peroxidase (GSH-px) also play an important role in the protection of cells against oxidative damage as anti-oxidative enzymes ( Olsvik et al, 2005 ; Damiano et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the vast majority of the studies support the notion that Cd exposure stabilizes Nrf2, prevents its degradation, and promotes its nuclear translocation as a protective mechanism [ 69 ]. This leads to the dose-dependent increase in the expression of Nrf2-downstream target genes [ 70 ], such as NQO1 and HO-1, in organs such as the liver [ 71 , 72 ] and spleen [ 73 ], as demonstrated in vivo by rodents studies but also in vitro by experiments on the astrocytoma cell line [ 74 ] and Mouse Embryonic Fibroblasts [ 2 ]. Lawal and Ellis (2011) speculated that Cd provokes nuclear Nrf2 activation by interacting with a specific G protein-coupled metal-binding receptor in macrophages and inducing phospholipase C. This event causes the release of intracellular Ca 2+ and diacylglycerol, both of which have the potential to modulate Nrf2 signaling [ 74 ].…”
Section: Determining Toxic Elements Role In Nrf2 Signalingmentioning
confidence: 99%
“…The authors concluded that the positive Nrf2 impact against Cd toxicity, such as the normalization of serum ALT and LDH activities after the Cd exposure and the attenuation of morphological liver alterations, can mostly be linked to the induction of genes involved in the antioxidant defense [ 77 ]. However, it was demonstrated that administration of a single CdCl 2 dose to mice can also contribute to the liver damage by inhibiting Nrf2 and HO-1 and activating inflammatory signaling pathways, NF-κB, NLRP3, and MAPKs [ 72 ]. Inhibition of Nrf2 was also found in mice testes accompanied by the decrease of Nrf2 downstream genes, GSH-Px, GCS, HO-1, and NQO1 [ 32 ].…”
Section: Determining Toxic Elements Role In Nrf2 Signalingmentioning
confidence: 99%
“…This is in agreement with a study which identified Nrf2 relevance in the detoxification response after AFB1 exposure, suggesting a Nrf2 chemoprotective role [ 38 ]. In general, loss of Nrf2 has been demonstrated to increase the sensitivity to several other toxic chemicals, such as acetaminofen, carbon tetrachloride, 3,5-Diethoxycarbonyl-1,4-dihydrocollidine (DDC), and cadmium chloride, highlighting a critical role of this transcription factor and its downstream target genes in acute and chronic liver damage [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Nrf2 In Acute Hepatotoxicitymentioning
confidence: 99%